Quantitative Electrochemical DNA Microarray on a Monolith Electrode with Ten Attomolar Sensitivity, 100 % Specificity, and Zero Background. Issue 3 (14th December 2017) - Raghunath, Shobana; Prasad, Abhijeet; Tevatia, Rahul; Gunther, Jillian.R.; Roy, Santanu; Krishnan, Sunil; Saraf, Ravi F.
Abstract: Circulating microRNA are promising diagnostic and prognostic biomarkers of disease in quantitative blood tests. A label‐free, PCR‐free, electrochemical microarray technology on a monolith electrode is described, with 10 attomolar (aM) sensitivity and responsiveness to binding of <1 zeptomole of target to immobilized ssDNA probes with zero background. Specificity is 100 % in a mixture with five nonspecific miRNA each with a 10 3 ‐fold higher concentration. Direct measurement on plasma‐derived miRNA without cDNA conversion and PCR demonstrated multiplexing and near‐ideal quantitative correlation with an equivalent pure sample. The dynamic range is a target concentration ranging from 10 −2 to 10 3 femtomolar (fM). This PCR‐free novel technology can be applied as a test for cancer diagnosis/prognosis to detect 10 3 copies of a miRNA sequence in RNA extracted from 100 μL of plasma. Abstract : Chip off the block : A DNA chip technology is developed to measure binding to a microarray on a monolith electrode by probing the local redox reaction on each spot. The redox peak, R max, was zero for nonbinding (ssDNA) and nonspecific binding. The binding is enhanced electrochemically in <30 mins to attain a 10 −2 to 10 3 femtomolar dynamic range. The method is applied to measure microRNA extracted from plasma with no PCR or cDNA conversion.